Symposium 8: Networking or going solo? : Understanding the Learner’s Perspective in the Flexible Learning Environment - Antman, Lotta; Larson, Lotty; Pilesjö, Petter (Proceedings of the International Conference on Networked Learning, 2006)
The question we set out to answer is: How do students in the LUMA-GIS programme go about their learning of GIS? The research question was approached from a phenomenographic perspective with the intention of generating descriptions and analyses of ways of experiencing the flexibility and the learning that is afforded in the programme. Data sources in this study included in-depth interviews and questionnaires (second-order data) as well as naturalistic data from submitted course work (first-order data). The entire population consisted of one hundred and ten students, who had finished the first course in the programme. Data is analysed and interpreted both from a quantitative and a qualitative perspective. Preliminary analysis of the data shows some interesting differences between students tendency to communicate with others in the course.